Predictors of performance improvements within a cognitive remediation program for schizophrenia - Scheu, Florian; Aghotor, Julia; Pfueller, Ute; Moritz, Steffen; Bohn, Francesca; Weisbrod, Matthias; Roesch-Ely, Daniela (Psychiatry research, 2013)
Cognitive impairment is regarded a core feature of schizophrenia and is associated with low psychosocial functioning. There is rich evidence that cognitive remediation can improve cognitive functions in patients with schizophrenia. However, little is known about what predicts individual remediation success. Some studies suggest that baseline cognitive impairment might be a limiting factor for training response. Aim of the current study was to further examine the role of cognitive and symptom variables as predictors of remediation success. We studied a total sample of 32 patients with schizophrenia and schizoaffective disorder who were engaged in a computer-based cognitive training program (CogPack). A pre-training test battery provided cognitive measures of selective attention, executive functioning, processing speed, verbal memory, and verbal intelligence along with measures for positive and negative symptoms. Training response was defined as improvement on training tasks. Correlation analyses revealed no significant relationship between any of the baseline cognitive or symptom measures and improvement rates. However, better baseline cognition was associated with a higher percentage of tasks with initial ceiling effects. We conclude that not carefully tailoring task difficulty to patients' cognitive abilities constitutes a much more severe threat to cognitive remediation success than cognitive impairment itself.
Gesehen am 07.02.2022